Hardware-in-Loop Simulation of PMSM in High Power Traction System - Lidong BU (机车电传动)
The control technology of high-power traction permanent magnet synchronous motor was studied in this paper. The system control strategy of permanent magnet motor based on asynchronous modulation mode, SHEPWM modulation mode and square wave mode was proposed. The engineering implementation of SHEPWM modulation mode and the dynamic switching method under different PWM modes were studied. The hardware-in-the-loop simulation results showed that the control strategy has good control performance in the full speed range, and the current was smooth and stable during the dynamic switching process.